Biogenesis of histone mRNAs in the yeast Saccharomyces cerevisiae - Canavan, Ruth Alice (Trinity College (Dublin, Ireland). Department of Microbiology, 2007)
The typical eukaryotic human diploid cell contains 3.2x10 9 base pairs of deoxyribonucleic acid (DNA) which, if presented in an extended form, would measure 1.2m in length. The large amount of DNA is tightly wrapped and compacted through its interaction with a set of small basic proteins called histones (Alberts et al, 2002). Histones are positively charged proteins that facilitate the folding of DNA. Four types of histones have been described: H2A, H2B, H3 and H4 (Baxevanis and Landsman, 1997). A 147 base pair segment of eukaryotic DNA associates with histones, forming an octameric protein complex known as the nucleosome (Baxevanis and Landsman, 1998; Grunstein and Mann, 1992). The quaternary structure of the nucleosome is stabilised through an interaction with an additional histone, H1. This structure is highly conserved. The level of compaction of DNA varies during the life cycle of the cell. During Interphase, chromatin is relatively decondensed and distributed throughout the nucleus. As cells enter mitosis, chromatin condenses into chromosome structures, which are relatively transcriptionally silent. As the cells undergo DNA replication, the newly formed DNA must be repackaged into chromatin. Therefore the production of histones is tightly controlled to ensure that maximum production occurs In the S-phase of the cell cycle (Xu et al, 1990).
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin